2022
DOI: 10.1007/s10518-022-01469-x
|View full text |Cite
|
Sign up to set email alerts
|

Analytical design models for geotechnical seismic isolation systems

Abstract: Geotechnical Seismic Isolation (GSI) can be defined as a new category of seismic isolation techniques that involve the dynamic interaction between the structural system and geo-materials. Whilst the mechanism of various GSI systems and their performance have already been demonstrated through different research methods, there is a missing link between fundamental research and engineering practice. This paper aims to initiate the development in this direction. A new suite of equivalent-linear foundation stiffnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 46 publications
(64 reference statements)
0
5
0
Order By: Relevance
“…The research conducted on the area of seismic isolation, has shown that the inclusion of rubber underneath a structure can work efficiently to protect structures against earthquakes, mainly through activating some efficient detuning-type mechanism. This is an outcome from numerical and analytical results (Tsang et al 2008(Tsang et al , 2009(Tsang et al , 2012(Tsang et al , 2019(Tsang et al , 2022Xu et al 2009;Pitilakis et al 2015;Brunet et al 2016). The results from numerical studies are backed up by physical testing, including shaking table tests (Xiong et al 2011;Xiong and Li 2013;Kaneko et al 2013;Nikitas et al 2014Nikitas et al , 2016Bandyopadhyay et al 2015;Tsiavos et al 2019;Yin et al 2022) and centrifuge tests (Tsang et al 2021).…”
Section: Introductionmentioning
confidence: 98%
“…The research conducted on the area of seismic isolation, has shown that the inclusion of rubber underneath a structure can work efficiently to protect structures against earthquakes, mainly through activating some efficient detuning-type mechanism. This is an outcome from numerical and analytical results (Tsang et al 2008(Tsang et al , 2009(Tsang et al , 2012(Tsang et al , 2019(Tsang et al , 2022Xu et al 2009;Pitilakis et al 2015;Brunet et al 2016). The results from numerical studies are backed up by physical testing, including shaking table tests (Xiong et al 2011;Xiong and Li 2013;Kaneko et al 2013;Nikitas et al 2014Nikitas et al , 2016Bandyopadhyay et al 2015;Tsiavos et al 2019;Yin et al 2022) and centrifuge tests (Tsang et al 2021).…”
Section: Introductionmentioning
confidence: 98%
“…Dynamic soil-foundation-structure interaction and its favourable effects can be facilitated in a controlled manner by modifying the foundation soils to lengthen the natural period of the system and dissipate seismic wave energy without causing undesirable permanent ground deformations. Half of the articles in this special issue focus on GSI systems that are based on this mechanism (Aloisio et al 2022;Bernal-Sanchez et al 2023;Chiaro et al 2022;Dhanya et al 2023;Edinçliler and Yildiz 2023;Tsang 2022;Vratsikidis and Pitilakis 2022). 2.…”
mentioning
confidence: 99%
“…Amongst these, rubber-soil mixtures have been the most researched materials (Bernal-Sanchez et al 2023;Chiaro et al 2022;Dhanya et al 2023; Forcellini and Alzabeebee 2022; Nikitas and Bhattacharya 2023; Vratsikidis and Pitilakis 2022), whilst there is a case study with the use of whole waste tyres (Hazarika et al 2023). Meanwhile, other materials have also been investigated, including EPS beads (Edinçliler and Yildiz 2023), geosynthetics (Banović et al 2022;Dhanya et al 2023), stone pebbles (Banović et al 2022), sand, timber and PVC (Tsiavos et al 2022), polyurethane (Gatto et al 2022), super absorbent polymers (SAP) (Somma and Flora 2023), as well as various high-damping (Aloisio et al 2022) and low-modulus materials (Tsang 2022).…”
mentioning
confidence: 99%
See 2 more Smart Citations